2014
DOI: 10.1007/s40265-014-0284-7
|View full text |Cite
|
Sign up to set email alerts
|

Turning a Molecule into a Medicine: the Development of Indacaterol as a Novel Once-Daily Bronchodilator Treatment for Patients with COPD

Abstract: Indacaterol is the first once-daily, long-acting β2-adrenergic agonist (LABA) approved for the treatment of chronic obstructive pulmonary disease (COPD). Indacaterol was developed using a combination of informed drug design and molecular chemistry to generate a β2-adrenergic agonist with a fast onset and long duration of action, enabling once-daily dosing with an acceptable safety profile. Early preclinical studies with indacaterol demonstrated these characteristics, and this promising molecule was taken into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 82 publications
0
11
0
Order By: Relevance
“…10,11 Furthermore, the differential sensitivity of different cell phenotypes to agonist-induced internalization of the β 2 -adrenoceptor may also have implications for drug therapy with inhaled longacting β 2 -agonists. 63,64 In summary, the present study has demonstrated the power of FCS in investigating cell surface β 2 -adrenoceptors at the very low expression levels often seen in endogenously expressing cells. FCS was able to detect SNAP-tagged β 2 -adrenoceptor expression in both ES-derived cardiomyocytes and CRISPR/Cas9 genome-edited HEK293T cells, where the expression level was too low to detect them using standard confocal microscopy.…”
Section: F I G U R Ementioning
confidence: 61%
“…10,11 Furthermore, the differential sensitivity of different cell phenotypes to agonist-induced internalization of the β 2 -adrenoceptor may also have implications for drug therapy with inhaled longacting β 2 -agonists. 63,64 In summary, the present study has demonstrated the power of FCS in investigating cell surface β 2 -adrenoceptors at the very low expression levels often seen in endogenously expressing cells. FCS was able to detect SNAP-tagged β 2 -adrenoceptor expression in both ES-derived cardiomyocytes and CRISPR/Cas9 genome-edited HEK293T cells, where the expression level was too low to detect them using standard confocal microscopy.…”
Section: F I G U R Ementioning
confidence: 61%
“…It was designed to have a quick onset of action (5 min), and ultra-long-acting duration, so it could be prescribed once daily. Indacaterol was initially approved in the EU in 2009 at doses of 150 - 300 µg; followed by 150 µg in Japan (2011), China (2012), and 75 µg in the US (2011) [ 40 ]. To date, indacaterol has been approved in more than 100 countries.…”
Section: Tiotropium and Labamentioning
confidence: 99%
“…Other pre-clinical and early clinical trials of indacaterol have been reviewed. 17 Indacaterol improved breathlessness in a meta-analysis of six trials. 18,19 A Cochrane systemic review analyzed 13 trials comparing indacaterol with either placebo or twice daily β-agonist in the treatment of COPD and demonstrated that indacaterol produced statistically and clinically meaningful increases in both lung function and quality of life compared with placebo.…”
Section: Dovepressmentioning
confidence: 99%